Fostering Quality of Reflection in First-Year Honours Students in a Bachelor Engineering Program Technology, Liberal Arts & Science (ATLAS) - Wilhelm, Pascal (Journal of Higher Education Theory and Practice, 2021)
This study focused on fostering the quality reflection displayed in semester self-evaluation reports (SERs) of first-year honours students in a bachelor engineering program Technology, Liberal Arts and Science (ATLAS). In a first pilot study, students’ conceptions of reflection and educational needs regarding reflection were explored. Based on the results and relevant theory, an intervention was designed. Twentynine participants, not previously exposed to academic training on reflection before, received a Reflection Guide on how to write reflections in their SERs. Two online interactive lectures were provided as support. Quality of reflection in the SERs was assessed using a standardized rubric and quality scores in the intervention group were compared with scores of the student cohort of the previous academic year (n = 33). Results showed that the intervention group reflected on a higher level than the comparison group. Perceived usefulness and value of the reflection method proposed were measured in both students and assessors. In general, both students and assessors were positive about the reflection method.